2019
DOI: 10.1155/2019/7065064
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodium falciparumandPlasmodium vivaxPrevalence in Ethiopia: A Systematic Review and Meta-Analysis

Abstract: Background. Malaria is a protozoan disease caused by the Plasmodium species. Among the five Plasmodium species known to infect human beings, Plasmodium falciparum and Plasmodium vivax malaria are by far the most predominant and widely distributed in Ethiopia. Malaria is one of the leading causes of morbidity and mortality globally, particularly in the sub-Saharan countries including Ethiopia. It is also a major obstacle to socio-economic development in the country. Methods. Articles were searched from PubMed, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
26
6

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 63 publications
7
26
6
Order By: Relevance
“…is study is nearly similar to systematic review and metaanalysis conducted among pregnant women in Ethiopia with the pooled prevalence of malaria 12.72% [41]. On the other hand, the result of this study was much lower than the previous research studies reported in Ethiopia among all age groups [39,42]. e comparative decrement of malaria prevalence in the current study might be related to life style change, geographical area, economic status, the type of malaria diagnosis methods used, and the time at which the study conducted [33].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…is study is nearly similar to systematic review and metaanalysis conducted among pregnant women in Ethiopia with the pooled prevalence of malaria 12.72% [41]. On the other hand, the result of this study was much lower than the previous research studies reported in Ethiopia among all age groups [39,42]. e comparative decrement of malaria prevalence in the current study might be related to life style change, geographical area, economic status, the type of malaria diagnosis methods used, and the time at which the study conducted [33].…”
Section: Discussionsupporting
confidence: 85%
“…Malaria causes serious complications in human, such as severe anaemia, acute renal failure, hypoglycemia [ 10 ], loss of productivity, school absenteeism, and other complications [ 38 ]. Therefore, the accurate malaria prevalence information is vital for the proper diagnosis, treatment, prevention, and policy preparation [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, when comparing the Rapid Diagnostic Test (RDT) results, malaria prevalence in 2015 (1.2 percent) was reduced compared to that of 2011 results (4.5 percent) [1]. The pooled prevalence of P. falciparum and P. vivax parasites estimates in a proportion of 62.8% and 37.2%, respectively [2]. There are different malaria diagnostic methods for malaria case management; the common and routine ones are patient's clinical assessment, microscopic examination of blood slides and the use of rapid diagnostic tests (RDTs).…”
Section: Introductionmentioning
confidence: 99%
“…Malaria transmission in Ethiopia is seasonal, depending mostly on altitude and rainfall, with a lag time varying from a few weeks before the beginning of the rainy season to more than a month after the end of the rainy season (Deressa et al, 2003;Tulu, 1993). From an agroecological perspective, the highest malaria prevalence was reported from a study conducted on mixed regions of low lands and midlands while the least was from low lands (Deress & Girma, 2019).…”
Section: Introductionmentioning
confidence: 99%